Предмет:
Другие предметыАвтор:
анонимПриводя дроби к общему знаменателю
( (a√a + b√b) / (√a + √b) - √(a * b) ) / (a - b) + 2 * √b / (√a + √b) =
= (1 / (√a + √b) ) * ( (a√a + b√b - (√a + √b) * √(a * b) ) / (a - b) + 2 * √b) =
= (1 / (√a + √b) ) * ( (a * √a + b * √b - a * √b - b * √a) / (a - b) + 2 * √b) =
= (1 / (√a + √b) ) * ( ( (a - b) * √a - (a - b) * √b) / (a - b) + 2 * √b) =
= (1 / (√a + √b) ) * ( ( (a - b) * (√a - √b) ) / (a - b) + 2 * √b) =
= (1 / (√a + √b) ) * (√a - √b + 2 * √b) = (1 / (√a + √b) ) * (√a + √b) = 1.
Ответ : 1.
Автор:
niki95Добавить свой ответ
Предмет:
Другие предметыАвтор:
анонимОтветов:
Смотреть
Предмет:
Другие предметыАвтор:
анонимОтветов:
Смотреть
Предмет:
Другие предметыАвтор:
анонимОтветов:
Смотреть
Предмет:
Другие предметыАвтор:
анонимОтветов:
Смотреть